Immigrant Castaways in the United Kingdom: Comparative Analysis of Virtudes (e misterios) by Xesús Fraga and Wilcza rzeka by Wioletta Grzegorzewska - Kołakowski, Marcin (Madrygal. Revista de Estudios Gallegos, 2026)
The article carries out a comparative and contrastive study of two autofictional novels, centered around the migratory experiences of two women: Virtudes (e misterios) (2020) by Xesús Fraga and Wilcza rzeka (2021) by Wioletta Grzegorzewska. It examines and compares the world and the experiences of immigrants (their spaces, social environment, language, the ethos of hard work, etc.) and the codification of the image of the host country. To achieve these ends, three methodological perspectives are used: literary comparativism, the sociology of migrations and studies on migrant literature. Likewise, the objective is to investigate to what extent the novels analyzed encode negative attitudes towards immigrants. In addition, the resistance and survival strategies that the protagonists are forced to adopt are discussed.